Pengendalian Biaya dan Waktu Menggunakan Metode EVM (Earned Value Management) pada Proyek Pembangunan Akses Sirkulasi Lapangan Gajah Mada - Saifuddin, Akhmat; Ridwan, Ahmad; Damara, Bobby (Universitas Batanghari Jambi, 2025)
Cost and time control using the EVM (Earned Value Management) method was carried out in the Gajah Mada Field Circulation Access Development project, Lamongan Regency. The purpose of this study is to find out whether the project performance based on cost and time is in accordance with the initial project plan or not. This study uses a descriptive quantitative method that aims to describe the project situation based on the results of systematic data analysis. The results of this study obtained a positive Cost Variant (CV) value, there was no negative Cost Variant value which indicates that there was no project cost overrun. The Cost Performance Index (CPI) greater than 1 indicates a positive value, meaning that more work has been completed than expenses. A positive Schedule Variant (SV) value indicates that during this period the project has accelerated the completion of project work from the planned schedule. Meanwhile, the value of the Schedule Performance Index (SPI) is greater than 1 which means that the completion of the project work is faster than the planned schedule. From the calculation of Estimate to Complete (ETC), it is concluded that the estimated cost for the remaining work is Rp. 1,337,436,973. while the calculation (EAC) of the total estimated total cost if the reporting of the 11th week of project performance remains the same until the end of the project, it is estimated to spend Rp. 5,986,736,672 which was originally planned to cost Rp. 6,299,864,092. For the estimated project completion time (EAS) Estimate All Schedule is 13,781 weeks which was originally planned for 14 weeks.